Structural evaluating of pier 24 of Maracaibo bridge subject to ship collision - Sarcos Portillo, Antonio; García Legl, Hildrun (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
On November 3, 1999, a ship, 7,000 ton weight, collided Pier 24 of Maracaibo Bridge. The Collision produced the spalling of concrete of the bent and destroyed six meters of the breakwater. The main purpose of this paper is to establish an analysis methodology in order to reproduce the structural response of the bridge due to the impact generated by collision. Also, it was necessary to know the stresses generated on the pier structural elements and to calculate cruise velocity when the collision was produced. Results showed that an important part of the energy was absorbed by the ship. The cruise velocity was calculated lower than 8 knot and during collision an opposite force to the initial ship thrust was generated in the superstructure.